Insights, Solutions and Empowerment: a framework for evaluating participatory design. Issue 1 (2nd January 2021) - Drain, Andrew; Shekar, Aruna; Grigg, Nigel
ABSTRACT: Participatory design (PD) has become a popular approach used in a range of applications to generate a range of different outcomes. The defining strength of this approach is that it has potential to generate appropriate solutions while also empowering the involved community. This strength has resulted in PD being used as a method for developing humanitarian technology in developing countries. However, this diversity has made it difficult to evaluate the effectiveness of each project, leading to criticisms that PD lacks empirically demonstrable benefits over traditional approaches. This article presents a new outcome-focused framework to assist in the evaluation of PD projects. The Insights, Solutions and Empowerment Framework draws from extant literature, and first-hand case studies in rural Cambodia, and attempts to provide a holistic view of the value PD offers, and important cross-cutting values to reflect on.